If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 5) + 4 = 9x + -3(x + -4) Reorder the terms: 6(5 + x) + 4 = 9x + -3(x + -4) (5 * 6 + x * 6) + 4 = 9x + -3(x + -4) (30 + 6x) + 4 = 9x + -3(x + -4) Reorder the terms: 30 + 4 + 6x = 9x + -3(x + -4) Combine like terms: 30 + 4 = 34 34 + 6x = 9x + -3(x + -4) Reorder the terms: 34 + 6x = 9x + -3(-4 + x) 34 + 6x = 9x + (-4 * -3 + x * -3) 34 + 6x = 9x + (12 + -3x) Reorder the terms: 34 + 6x = 12 + 9x + -3x Combine like terms: 9x + -3x = 6x 34 + 6x = 12 + 6x Add '-6x' to each side of the equation. 34 + 6x + -6x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 34 + 0 = 12 + 6x + -6x 34 = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 34 = 12 + 0 34 = 12 Solving 34 = 12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3+4(3x-4)=5-5(2x+1) | | 8+4(4x-6)=9-5(2x+1) | | 2(x+7)=9x+8-7x-6 | | 7x^2-5x+7=0 | | 0.4(3z+6)+18.6=0.6(3z-5) | | Jah= | | 3.4x=2.7x+4.2 | | x^2-(-12x)+32=0 | | 9x-4y=-34 | | x+(3+x)=41 | | 3(-1)+2y=3 | | 6x+7y=31 | | 3-2y=-9 | | 3-2=-9 | | 9(z+2)-3(z-2)=3(z-2)+2(z-1) | | X^2+ax+a+2=0 | | 4(2x-7)-3=4(x-3)+5 | | 2=.8x^2+1.8x | | -.25[-4+(-5)]+a=16.25 | | 16x-(8x-9)=65 | | 3(6z+1)-7=104 | | 2x-7x+17=3x+25 | | 5x+7x-4x=18+6 | | x(x+5)=126 | | -8(-3-6)+a=86 | | -8p=8 | | -8b+7-4=23 | | -m=40 | | 5p-9p=12 | | -3y+3=-12 | | 13=4x+4 | | x^3-2*x^2-44x-171=0 |